ORBIS (Open Research Biopharmaceutical Internships Support) – building bridges between academia and pharmaceutical industry to improve drug development - Jakubowska, Emilia; Davin, Sharon; Dumicic, Aleksandra; Garbacz, Grzegorz; Juppo, Anne; Michniak-Kohn, Bożena; Rudzki, Piotr J.; Smułek, Wojciech; Strachan, Clare; Syarkevych, Oleg; Tajber, Lidia; Lulek, Janina (Journal of Medical Science, 2020)
Open Research Biopharmaceutical Internships Support (ORBIS) is an international, Horizon 2020 project funded by Maria Skłodowska-Curie Actions, Research and Innovation Staff Exchange (RISE) programme. Six academic institutions and four pharmaceutical companies from seven countries cooperate with the aim to improve the preclinical pathway of medicine development through increased Research and Development (R&D) productivity, especially focusing on processes and technologies which address the challenge of poor drug bioavailability. The RISE scheme supports secondments, meaning that early stage and experienced researchers are sent to consortium partner institutions to advance studies on pharmaceutical preformulation, dosage forms and drug delivery systems and methods of biopharmaceutical evaluation. The ORBIS project enables secondees to gain news skills and develop their competences in an international and intersectoral environment, strengthening the human capital and knowledge synergy in the European pharmaceutical R&D sector.